Developing net-zero carbon supply chains in the European manufacturing industry – a multilevel perspective - Steiner, Benedikt; Münch, Christopher; Beckmann, Markus; von der Gracht, Heiko (Supply Chain Management-An International Journal, 2024)
Purpose: The European Union (EU) and European companies are striving for net-zero carbon targets by 2050 and are therefore focused on urgent decarbonization efforts. Manufacturing contributes to 20% of European carbon emissions, although the primary challenge lies in supply chain (SC) emissions, which highlights the field's need to transform. Amid the dissonance between public and private net-zero commitments and persistent carbon emissions, uncertainties surround the development of net-zero carbon supply chains (NZCSCs). This paper aims to address this lack of knowledge by presenting an exploration of the development of NZCSCs within the EU through 2050. Design/methodology/approach: Using a real-time Delphi methodology and tool from durvey.org, this study involves a multiphase panel discussion process with 67 SC and sustainability experts. Twelve prospective theses for NZCSC development in the EU were formulated through desk research, interviews and an expert workshop. The panel assessed these theses in terms of impact, desirability and anticipated occurrence year and provided justification for their evaluations. Findings: The study identifies three clusters that influence NZCSC development, comprising 68 implications that scholars, managers and policymakers should consider during this transition. Originality/value: This study contributes to the available information regarding NZCSCs by offering insights from a multilevel perspective into the influences on NZCSC development in the EU's manufacturing sector.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Carbon footprint; Delphi; EU; Europe; Low carbon; Manufacturing; Manufacturing industry; Multilevel perspective; Net-zero carbon emission